Relationship Between Symptoms and Motoric Subtype of Delirium - Meagher, David J; O'Hanlon, Donal; O'Mahony, Edmond; Casey, Patricia R; Trzepacz, Paula T (The journal of neuropsychiatry and clinical neurosciences, 2000)
For 46 patients with delirium who were consecutive referrals to a consultation-liaison psychiatry service, the authors describe the relationships between symptoms, as rated on the Delirium Rating Scale, and delirium motoric subtypes, as defined by Liptzin and Levkoff's criteria. Most cases were of the mixed subtype (46%), 24% were hypoactive, and 30% were hyperactive. Overall scores differed significantly among motoric subtype groups, being highest in the hyperactive, lowest in the hypoactive, and intermediate in the mixed. On item scores, the hypoactive group scored lower than the hyperactive group for delusions, mood lability, sleep-wake cycle disturbances, and variability of symptoms, but lower than the mixed group only for mood lability. The results suggest that delirium presents as motoric subtypes that differ according to symptom profile and severity of delirium. These subtypes may differ in their underlying pathophysiologies, responsiveness to therapeutic interventions, and outcome.